2022
DOI: 10.1093/eurheartj/ehac544.2473
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding high- vs low-intensity resistance training to endurance training in patients with heart failure: preliminary results of a randomized controlled trial

Abstract: Background In current ESC/EAPC guidelines, adding resistance training to endurance training is advised for patients with heart failure (HF), but the optimal intensity of the resistance training is unknown (40–80% of 1RM is advised). Purpose To investigate the effects of high- vs low-intensity resistance training as an adjunct to endurance training on: aerobic capacity (primary outcome), walking capacity, muscle strength and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…28 Similar RT approach was also recently replicated in patients with HF, whereas the study has demonstrated similar improvements in CRF, maximal muscle strength, and quality of life following HL-RT and LL-RT, with no adverse CV events. 29 These novel findings provide a complimentary evidence to those presented in the review by Bjarnason-Wehrens et al, 18 and extend the possibilities of using different RT approaches to optimize the exercise-based CR directly from the enrollment with a possibility to readjusting RT load according to improvement during the CR. 26,29,30 On the basis of the novel evidence, experts in preventive cardiology have developed a digital training and decisive support system (Exercise Prescription in Everyday practice & Rehabilitative Training tool) to enable clinicians to optimize RT prescription in patients with CAD and HF and to finally reach international consensus among leading preventive cardiology organizations.…”
Section: The (Bright) Future Of Rt In Crsupporting
confidence: 70%
See 2 more Smart Citations
“…28 Similar RT approach was also recently replicated in patients with HF, whereas the study has demonstrated similar improvements in CRF, maximal muscle strength, and quality of life following HL-RT and LL-RT, with no adverse CV events. 29 These novel findings provide a complimentary evidence to those presented in the review by Bjarnason-Wehrens et al, 18 and extend the possibilities of using different RT approaches to optimize the exercise-based CR directly from the enrollment with a possibility to readjusting RT load according to improvement during the CR. 26,29,30 On the basis of the novel evidence, experts in preventive cardiology have developed a digital training and decisive support system (Exercise Prescription in Everyday practice & Rehabilitative Training tool) to enable clinicians to optimize RT prescription in patients with CAD and HF and to finally reach international consensus among leading preventive cardiology organizations.…”
Section: The (Bright) Future Of Rt In Crsupporting
confidence: 70%
“…29 These novel findings provide a complimentary evidence to those presented in the review by Bjarnason-Wehrens et al, 18 and extend the possibilities of using different RT approaches to optimize the exercise-based CR directly from the enrollment with a possibility to readjusting RT load according to improvement during the CR. 26,29,30 On the basis of the novel evidence, experts in preventive cardiology have developed a digital training and decisive support system (Exercise Prescription in Everyday practice & Rehabilitative Training tool) to enable clinicians to optimize RT prescription in patients with CAD and HF and to finally reach international consensus among leading preventive cardiology organizations. 31 Apart from the optimization of RT in the majority of patients enrolled in CR (eg, patients with CAD and HF), there are also other populations of patients with CVD, which would benefit from the enrollment into RT but were not presented in the present review.…”
Section: The (Bright) Future Of Rt In Crsupporting
confidence: 70%
See 1 more Smart Citation